Triterpene Saponins from the Roots of Ilex asprella. Issue 5 (May 2014) - Lei, Yu; Shi, She‐Po; Song, Yue‐Lin; Bi, Dan; Tu, Peng‐Fei
Abstract Six new triterpene saponins, ilexasprellanosides A–F (1–6, resp.), together with eleven known compounds were isolated from the roots of Ilex asprella. The new saponins were characterized as ursa‐12, 18‐dien‐28‐oic acid 3‐O‐β‐D‐xylopyranoside (1), 19α‐hydroxyursolic acid 3‐O‐β‐D‐(2′‐O‐acetylxylopyranoside) (2), 19α‐hydroxyursolic acid 3‐O‐β‐D‐glucuronopyranoside (3), 3β, 19α‐dihydroxyolean‐12‐en‐23, 28‐dioic acid 28‐O‐β‐D‐glucopyranoside (4), 19α‐hydroxyoleanolic acid 3‐O‐β‐D‐(2′‐O‐acetylxylopyranoside) (5), 19α‐hydroxyoleanolic acid 3‐O‐β‐D‐glucuronopyranoside (6). The structures of the new compounds were elucidated by analysis of their spectroscopic data and chemical degradation. Compounds 2, 4, oleanolic acid 3‐O‐β‐D‐glucuronopyranoside, 3‐β‐acetoxy‐28‐hydroxyurs‐12‐ene, and pomolic acid showed significant cytotoxic activities against human tumor cell line A549 (IC50 values of 1.87, 2.51, 1.41, 3.24, and 5.63 μM, resp.).